Associations between testosterone and metabolic syndrome in depressed and non‐depressed older men and women. (3rd January 2019) - de Wit, Anouk E.; Giltay, Erik J.; de Boer, Marrit K.; Bosker, Fokko J.; van der Mast, Roos C.; Comijs, Hannie C.; Oude Voshaar, Richard C.; Schoevers, Robert A.
Abstract : Objectives: Older age and major depressive disorder (MDD) are both risk factors for the development of cardiovascular diseases. Testosterone has been associated with MDD and metabolic syndrome (MetS) in men, although associations in women are less clear. Therefore, we investigated whether testosterone is associated with MetS and whether this association is different for depressed and non‐depressed older men and women. Methods: In this prospective cohort study, 478 participants (349 patients with MDD and 129 controls) aged between 60 and 93 years from the Netherlands Study of Depression in Older Persons were included. Total testosterone (TT) and sex‐hormone binding globulin levels were measured using a second‐generation radioimmune assay. Free testosterone (FT) was calculated based on TT. MetS was defined according to the National Cholesterol Education Program Adult Treatment Panel III criteria. Results: A higher risk for MetS was found in men with low FT and TT (odds ratio [OR]: 0.67, 95% confidence interval [95%CI]: 0.47‐0.95 and OR: 0.51, 95%CI: 0.34‐0.75), and in women with high FT (OR: 1.41, 95%CI: 1.08‐1.82). Strong associations in the same direction were found with adiposity, glucose, and plasma lipid MetS components at baseline, but not with changes in these components at 2‐year follow‐up. The associations did not significantly differ between MDD patients and controls. Conclusions: Independently of having MDD, low testosterone levels in men and, in contrast, high testosterone levels in women were significantly associated with MetS and its components.